Deaggregation of In Vitro-Degranulated Human Platelets: Irreversibility of Aggregation May Be Agonist-Specific Rather Than Related to Secretion Per Se - Bauman, Joan E; Joachim Reimers, H; Heinrich Joist, J (Thrombosis and Haemostasis, 1987)
Based on studies with thrombin, it has been proposed that human platelets exposed to strong release-inducing agents undergo irreversible aggregation and cannot be deaggregated without the use of proteolytic enzymes. We tested the hypothesis that irreversible human platelet aggregation occurs as a result of thrombin-specific platelet alterations rather than induction of the release reaction per se. Washed human platelets were exposed to either thrombin (THR) or the aminophospholipid N-(7-Nitro- 2,1,3-benzoxydiazol-4-yl) phosphatidylserine (NBD-PS) for 20 seconds. Both agents caused similarly extensive release of platelet dense- and α-granule contents. After neutralization of thrombin and NBD-PS, and addition of PGE1 and apyrase, the platelets were sedimented, resuspended and incubated at 37° C with gentle agitation. Single, disc-shaped, degranulated platelets which were recovered in both systems were capable of aggregation in response to a second exposure to aggregating and release- inducing stimuli. Deaggregation was more rapid, more extensive, and more reproducible with NBD-PS- than with THR-degranulated platelets. Platelets exposed to thrombin for longer than 20 seconds showed a progressive loss of deaggregability which was not observed after prolonged incubation with NBD-PS. These findings do not support the concept that extensive secretion per se causes irreversible aggregation of human platelets. Instead it appears that formation of irreversible linkages between platelets involves the specific, time-dependent interaction of THR with platelets, released fibrinogen and possibly one or more other substances secreted from platelets.
Keywords: Irreversible platelet aggregation; Thrombin; NBD-phosphatidylserine